(untitled) (Web of Teachers: Inderscience Research, 2024)
In order to develop, improve and independently make the educational system more efficient, the main issues of simplifying the state’s complex educational criteria, using innovative technologies, modernizing educational programs and improving the quality of education are considered. Within the framework of this strategy, some major studies, such as increasing scientific and pedagogical potential, quality teaching requirements and independent and effective directions of education, use of innovative methods for managing modern classrooms, educational calculations and development of methodological tools, development of the monitoring system of educational processes, paying attention to the moral and physical development of students, educating and providing perspective, there are several other directions.